Analyze Students’ Difficulty Learning Course DAS 16403 Cell Biology of Diploma in Applied Science - Nurazrina Faeiza ,; Nur Najihah,; Nordin, Norbaizura (Multidisciplinary Applied Research and Innovation, 2024)
The students of Diploma in Applied Science had been struggling to learn the Cell Biology course established. Thus, the purpose of this project that we handled is to prevent the students from difficulty in learning and also to avoid them from repeating a course or experiencing a substandard pointer and to keep the student’s performance in university. The objectives in this project are to determine the most difficult course to score among students of Diploma in Applied Science in UTHM, to determine the reasons why it is hard for students of Diploma in Applied Science in UTHM to excel the Cell Biology course and to determine the difficulty of learning the course experienced by the students of Diploma in Applied Science in UTHM. The targeted society for our project is the student of Diploma in Applied Science in UTHM in session 2021/2022 and 2022/2023. The study focuses on the difficult course based on the data of student’s grade in other to make a conclusion. Besides, this project also focuses on several ways to overcome the problem to learn the course so that the students will not fail and repeat the course for the next semester which could delay their time to graduate on exact time same as other students. The quantitative research methodology used for this project successfully implemented. We found that majority students have same opinion that Cell Biology is a course that has many facts to memorise and take time to understand it. In conclusion, the students of Diploma in Applied Science in UTHM had some difficulties in order to learn and excel the Cell Biology course.